2022
DOI: 10.3389/fmed.2022.817957
|View full text |Cite
|
Sign up to set email alerts
|

Acidic Electrolyzed Water Inhibits the Viability of Gardnerella spp. via Oxidative Stress Response

Abstract: The vaginal microbiota, dominated by Lactobacilli, plays an important role in maintaining women's health. Disturbance of the vaginal microbiota allows infection by various pathogens such as Gardnerella spp. (GS) and related anaerobic bacteria resulting in bacterial vaginosis (BV). At present, the treatment options for BV are extremely limited. Treatment of antibacterial drugs and vaginal acidification are the two primary therapeutic methods. Acid electrolyzed water (AEW) is known to inactivate microorganisms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Therefore, non-antibiotic agents, such as non-electrolyzed acidic water, might be highly effective and safe for the treatment of both antibiotic susceptibility and resistance to H. pylori bacteria [32]. Several studies on HOCl have shown its numerous effects on various pathogenic bacteria, including H. pylori infection [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, non-antibiotic agents, such as non-electrolyzed acidic water, might be highly effective and safe for the treatment of both antibiotic susceptibility and resistance to H. pylori bacteria [32]. Several studies on HOCl have shown its numerous effects on various pathogenic bacteria, including H. pylori infection [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Also, it had a negligible effect on L. acidophilus . Furthermore, vaginal samples were collected from women with BV and the new treatment was able to eliminate all the microbial viability in the cultured samples (Zhao et al, 2022 ).…”
Section: Promising Alternative Strategies For Bv Treatmentmentioning
confidence: 99%